1985
DOI: 10.1063/1.96342
|View full text |Cite
|
Sign up to set email alerts
|

Growth by molecular beam epitaxy and characterization of InAs/GaAs strained-layer superlattices

Abstract: InAs/GaAs superlattices with ultra-thin InAs (few monolayer) were grown on GaAs substrates. Nucleation of InAs occurs in a two-dimensional or a three-dimensional way depending on the growth conditions. The physical properties: x ray, transmission electron microscopy, and photoluminescence were used to characterize the different growth processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
319
0
9

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 859 publications
(331 citation statements)
references
References 6 publications
3
319
0
9
Order By: Relevance
“…The energy position of the In peaks suggests the presence of a continuous film underlying the islands, this is in agreement with other literature results [9,10] which indicate that the InAs/GaAs system grows in the Stransky-Krastanov mode with a 1.7 ML thick film wetting the substrate. We tried to simulate the spectra by assuming the presence of a 1, 2 or 3 ML thick continuous film (the integer ML steps were chosen for computational ease) and we found that for all the samples a 2ML film at the interface best simulates the trailing edge of the spectra.…”
Section: Resultssupporting
confidence: 81%
“…The energy position of the In peaks suggests the presence of a continuous film underlying the islands, this is in agreement with other literature results [9,10] which indicate that the InAs/GaAs system grows in the Stransky-Krastanov mode with a 1.7 ML thick film wetting the substrate. We tried to simulate the spectra by assuming the presence of a 1, 2 or 3 ML thick continuous film (the integer ML steps were chosen for computational ease) and we found that for all the samples a 2ML film at the interface best simulates the trailing edge of the spectra.…”
Section: Resultssupporting
confidence: 81%
“…19 A means to adjust stratification without altering the starting composition or the deposition method would offer a huge efficiency gain over conventional fabrication technology. 6,[20][21][22] Our vision in the design of a switchable, stratified coating is to draw upon insights from our earlier work 23 to bring together two different materials technologies: colloidal stratification and pH-responsive particles. Here, we show how the stratification of binary particle blends can be switched off (or on) simply by raising (or lowering) the pH of the initial dispersion.…”
mentioning
confidence: 99%
“…The fluctuation in the size of these self-organized quantum dots can be as small as 10%, and the InAs QD's are typically 10 nm in diameter and about 4 nm high depending on the growth conditions. 2,3 For ion-beam analysis experiments, the QD sample was placed in a three-axes goniometer with an angular resolution Ͻ0.005°. 4 Channeling experiments have been performed using 4-MeV He ϩ ions from the 2-30-MeV AVF Cyclotron at the Eindhoven University of Technology.…”
Section: Methodsmentioning
confidence: 99%